Computerized heat loss evaluation of farrowing houses - George, H.C.; Spillman, C.K.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Accurate and concise heat loss analysis is available through a computer program to help producers. The economic benefit of insulating a new structure or increasing the insulation level of each of the building parts (ceiling, walls, windows, etc.) is calculated by the program. Ventilation is evaluated to assist the swine producer in understanding proper ventilation rates.
Keywords: Swine; Heat loss; Farrowing houses; Ventilation